(untitled) (Al-Qamar, 2022)
The purpose of this research paper is to describe that the religion and human life are inseparable. According to the Holy Qur’an, life and death are also creations of the Almighty, of whom we and this universe are created. This Almighty has combined human with two parts, material existence (body) and immaterial existence (soul). He has created the equipment for the training and evolution of material existence in the form of this system of the universe, and he has also explained the method of providing the means of life from this system of the universe. In the same way, the rules of immaterial existence which is the ruler of material existence have also been explained by the prophet, which is called religion in general terms. These religious precepts, in fact, serve the purpose of admiring human character and deeds, and on them the beauty of society is based. Thus the right to express the rules of human constructive character belongs to the very being, which created human life. All of these precepts apply perfectly to Islam and Judaism, but the issue of Christianity is different. The Christian religious book does not claim to be inspired, nor do its contents confirm its inspiration. The basic creeds of Christianity also lack the support of the Gospels. In Christianity, no educational material seems to be attributed to Jesus. Perhaps that is why we do not see any proud society under the shadow of Christian teachings in history. On the contrary, the existence of councils, the Great Schism, accountability, the reform movement and the conflict of religion and state in Christian history deny that Christianity is a constructive religion. For these reasons, the future of Christianity, one of the world’s two major religions, does not look bright. The future of humanity seems to depend on the world’s second largest religion, and that religion is Islam.